Pick Up Strategy dalam Upaya Meningkatkan Intensi Menabung Pedagang di Pasar Gemblegan - Krisnawati Krisnawati; Risda Frestiana; Rofifah Aisyah Luthfi; Susilaningsih Susilaningsih (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This study aims to increase savings intentions, especially for people who work as traders in the market by using a strategy, namely a pick-up strategy. The method used in this research is a qualitative method with an exploratory descriptive approach. .The results of the research show that the financial management of traders in the Gemblegan market is still relatively poor, so in this case banking agencies take a role so that people's needs can be met, namely by implementing a pick up strategy. Based on the results of interviews conducted with three traders, they stated that by implementing this strategy they felt their desire to save was getting higher and their needs were also helped by the results of implementing the pick up strategy.